(untitled) (Comprehensive Journal of Science, 2026)
students in Al-Zahraa Educational Institutions. The research sample consisted of 76 students, 38 males and 38 females. The researcher used the Shyness Scale developed by Hussein Al-Darini (1998). The results indicated a high level of shyness among the students in the research sample. Furthermore, the results showed statistically significant differences at the 0.01 level between males and females based on gender, favoring females.